Systemic mapping of organ plasma extravasation at multiple stages of chronic heart failure - Kitzerow, Oliver; Suder, Paul; Shukry, Mohanad; Lisco, Steven J.; Zucker, Irving H.; Wang, Han-Jun (Frontiers in Physiology, 2023)
Chronic Heart failure (CHF) is a highly prevalent disease that leads to significant morbidity and mortality. Diffuse vasculopathy is a common morbidity associated with CHF. Increased vascular permeability leading to plasma extravasation (PEx) occurs in surrounding tissues following endothelial dysfunction. Such micro-and macro-vascular complications develop over time and lead to edema, inflammation, and multi-organ dysfunction in CHF. However, a systemic examination of PEx in vital organs among different time windows of CHF has never been performed. In the present study, we investigated time-dependent PEx in several major visceral organs including heart, lung, liver, spleen, kidney, duodenum, ileum, cecum, and pancreas between sham-operated and CHF rats induced by myocardial infarction (MI). Plasma extravasation was determined by colorimetric evaluation of Evans Blue (EB) concentrations at 3 days, ~10 weeks and 4 months following MI. Data show that cardiac PEx was initially high at day 3 post MI and then gradually decreased but remained at a moderately high level at ~10 weeks and 4 months post MI. Lung PEx began at day 3 and remained significantly elevated at both ~10 weeks and 4 months post MI. Spleen PEx was significantly increased at ~10 weeks and 4 months but not on day 3 post MI. Liver PEx occurred early at day 3 and remain significantly increased at ~10 weeks and 4 months post MI. For the gastrointestinal (GI) organs including duodenum, ileum and cecum, there was a general trend that PEx level gradually increased following MI and reached statistical significance at either 10 weeks or 4 months post MI. Similar to GI PEx, renal PEx was significantly elevated at 4 months post MI. In summary, we found that MI generally incites a time-dependent PEx of multiple visceral organs. However, the PEx time window for individual organs in response to the MI challenge was different, suggesting that different mechanisms are involved in the pathogenesis of PEx in these vital organs during the development of CHF.